Sun protective behaviors and vitamin D levels in the US population: NHANES 2003–2006 - Linos, Eleni (2011)
BACKGROUND: Sun protection is recommended for skin cancer prevention, yet little is known about the role of sun protection on vitamin D levels. Our aim was to investigate the relationship between different types of sun protective behaviors and serum 25(OH)D levels in the general US population. METHODS: Cross-sectional, nationally representative survey of 5,920 adults aged 18–60 years in the US National Health and Nutrition Examination Survey 2003–2006. We analyzed questionnaire responses on sun protective behaviors: staying in the shade, wearing long sleeves, wearing a hat, using sunscreen and SPF level. Analyses were adjusted for multiple confounders of 25(OH)D levels and stratified by race. Our primary outcome measures were serum 25(OH)D levels (ng/ml) measured by radioimmunoassay and vitamin D deficiency, defined as 25(OH)D levels <20 ng/ml. RESULTS: Staying in the shade and wearing long sleeves were significantly associated with lower 25(OH)D levels. Subjects who reported frequent use of shade on a sunny day had −3.5 ng/ml (p(trend) < 0.001) lower 25(OH)D levels compared to subjects who reported rare use. Subjects who reported frequent use of long sleeves had −2.2 ng/ml (p(trend) = 0.001) lower 25(OH)D levels. These associations were strongest for whites, and did not reach statistical significance among Hispanics or blacks. White participants who reported frequently staying in the shade or wearing long sleeves had double the odds of vitamin D deficiency compared with those who rarely did so. Neither wearing a hat nor using sunscreen was associated with low 25(OH)D levels or vitamin D deficiency. CONCLUSIONS: White individuals who protect themselves from the sun by seeking shade or wearing long sleeves may have lower 25(OH)D levels and be at risk for vitamin D deficiency. Frequent sunscreen use does not appear to be linked to vitamin D deficiency in this population.